Experimentation on generating two-dimensional quasi-random sequences - Chương, Vũ Hoài (Journal of Computer Science and Cybernetics, 2012)
Halton/Hammersley sequences, the most well-known and widely used multi-dimensional quasirandom sequences, are constructed by combining van der Corput sequences with on another or with $k/N$ sequence. We attempt to generate two-dimensional sequences by combining two simple one-dimensional sequences ($k/N$, mid-point, $V$, van der Corput, Richtmyer, pseudorandom sequences) and experimentally receive many lowest discrepancy sequences.